The UDP-glucose pyrophosphorylase from Giardia lamblia is redox regulated and exhibits promiscuity to use galactose-1-phosphate - Ebrecht, Ana Cristina (2015)
Background: Giardia lamblia is a pathogen of humans and other vertebrates. The synthesis of glycogen and of structural oligo and polysaccharides critically determine the parasite's capacity for survival and pathogenicity. These characteristics establish that UDP-glucose is a relevant metabolite, as it is a main substrate to initiate varied carbohydrate metabolic routes. Results: Herein, we report the molecular cloning of the gene encoding UDP-glucose pyrophosphorylase from genomic DNA of G. lamblia, followed by its heterologous expression in Escherichia coli. The purified recombinant enzyme was characterized to have a monomeric structure. Glucose-1-phosphate and UTP were preferred substrates, but the enzyme also used galactose-1-phosphate and TTP. The catalytic efficiency to synthesize UDP-galactose was significant. Oxidation by physiological compounds (hydrogen peroxide and nitric oxide) inactivated the enzyme and the process was reverted after reduction by cysteine and thioredoxin. UDP-N-acetyl-glucosamine pyrophosphorylase, the other UTP-related enzyme in the parasite, neither used galactose-1-phosphate nor was affected by redox modification. Conclusions: Our results suggest that in G. lamblia the UDP-glucose pyrophosphorylase is regulated by oxido-reduction mechanism. The enzyme exhibits the ability to synthesize UDP-glucose and UDP-galactose and it plays a key role providing substrates to glycosyl transferases that produce oligo and polysaccharides. General significance: The characterization of the G. lamblia UDP-glucose pyrophosphorylase reinforces the view that in protozoa this enzyme is regulated by a redox mechanism. As well, we propose a new pathway for UDP-galactose production mediated by the promiscuous UDP-glucose pyrophosphorylase of this organism.